Primaquine dipeptide derivatives bearing an imidazolidin-4-one moiety at the N-terminus as potential antimalarial prodrugs - Nuno Vale (2009)
Primaquine dipeptide derivatives bearing an imidazolidin-4-one moiety at the N-terminus were synthesized and evaluated as potential transmission-blocking antimalarial prodrugs. All compounds were hydrolyzed to the parent dipeptide derivative of primaquine in neutral and basic solutions, with half lives ranging from 0.7 to 31 h at 37 degrees C, depending on the nature of the substituents present in the imidazolidin-4-one moiety and in the C-terminal amino acid directly coupled to primaquine. The antimalarial activity was studied for selected compounds using a model consisting of Plasmodium berghei, UK mice and Anopheles stephensi mosquitoes. The imidazolidin-4-one derived from Ala-Ala-primaquine and acetone reduced the transmission of the infection to mosquitoes more efficiently than primaquine as shown by the significant decrease in the number of oocysts in the midguts of the mosquitoes at 10 and 50 mu mol/kg when compared to the control.